Case report: A case of giant accessory hepatic lobe torsion combined with left hepatic vein branch thrombosis in a child - Xiangang Xiong; Xiangang Xiong; Yonghua Lou; Teng Zhou; Teng Zhou; Zebing Zheng; Zebing Zheng; Yuanmei Liu; Yuanmei Liu; Rui Liu; Rui Liu; Kaizhi Zhang; et al. (Frontiers Media S.A., 2022)
The accessory hepatic lobe (AHL) is a rare congenital malformation of the hepatic tissue, among which the giant AHL is the rarest in children. Patients without complications are usually asymptomatic, and most auxiliary examinations cannot provide a definitive preoperative diagnosis. Surgical procedure is the only recommended management for patients who suffered from the complications of AHL. We report the case of a rare pediatric giant AHL torsion combined with left hepatic vein branch thrombosis which was successfully treated by laparoscopic lobectomy followed by excision of AHL.